(untitled) (Biological Sciences - PJSIR, 1998)
The fate of soil chemical characteristics as a function of ground water irrigation was observed at Shahzadpur Thana under the district of Sirajgonj. The chemical analysesviz pH, EC, organic carbon, N, P, K, Ca, Mg, S, Zn, Fe, Cu, Mn, Band Na were performed on 20 irrigated and respective 20 non-irrigated soils. Before irrigation, soil pH was neutral to slightly alkaline. Irrigation did not bring remarkable change on soil pH but increased EC significantly (EC of non-irrigated soil was 2.16-3.34 Scm’ and that of irrigated soil was 2.66-4.34 Scm’). Potassium, calcium and magnesium contents of soils were also increased significantly by the irrigation whereas, the remaining nutrients were not affected significantly.